1993
DOI: 10.1093/oxfordjournals.humrep.a138137
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of 63 couples with a history of recurrent spontaneous abortion: contributing factors and outcome of subsequent pregnancies

Abstract: To evaluate the possible causes of recurrent spontaneous abortion (RSA) and to elucidate the prognosis for subsequent pregnancies 63 RSA patients were studied. Parental karyotyping revealed chromosomal aberrations in six of the 63 couples (4.8%). The rate of increased concentrations of antibodies against cardiolipin was comparable in the patients (10.0%) and in 30 parous controls (6.7%), as was also the occurrence of other autoantibodies (43.3 and 36.7%, respectively). Hysteroscopy revealed uterine cavity abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 0 publications
3
47
0
3
Order By: Relevance
“…The incidence of pregnancy complications like spontaneous abortion, preterm birth, and intrauterine growth retardation were found in 16.67, 13.33, and 26.67 % of pregnancies, respectively. Similar observation was found in the series published by Tulppala et al [20] who conducted a prospective study of 32 deliveries in 63 women with RPL and found that pregnancy complications like preterm delivery and IUGR were 9.7 and 20 %, respectively, in these women.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of pregnancy complications like spontaneous abortion, preterm birth, and intrauterine growth retardation were found in 16.67, 13.33, and 26.67 % of pregnancies, respectively. Similar observation was found in the series published by Tulppala et al [20] who conducted a prospective study of 32 deliveries in 63 women with RPL and found that pregnancy complications like preterm delivery and IUGR were 9.7 and 20 %, respectively, in these women.…”
Section: Discussionsupporting
confidence: 89%
“…The diverse aetiologies associated with RSA, include chromosomal alterations (Stephenson et al, 2002), maternal and foetal structural abnormalities (Philipp et al, 2003, Salim et al, 2003, thrombophilic disorders (Rey et al, 2003) and autoimmune disorders such as the antiphospholipid syndrome (Levine et al, 2002). Nevertheless, in ~50 % of the cases the aetiology remains unknown (Li et al, 2002, Plouffe et al, 1992Tulppala et al, 1993), indicating that the underlying aetiological grounds constitute a complex lattice of genetic and environmental causes. Previous attempts to describe genetic factors using the candidate gene approach have been relatively unsuccessful (Kaare et al, 2006, Kaare et al, 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous prospective studies, the effect of ACA on live birth rate has been reported comparable to our researcher, which has a negative impact on live birth. 24,14,17 The limitations of the present study are its smaller sample size and single centre study; however, our study does not differ from previously reported studies on this topic.…”
Section: Discussionmentioning
confidence: 56%
“…7,[9][10][11][12][13][15][16][17] In the prospective studies, the effect of ACA on live birth rate has been reported very differently, The different results in the prospective studies could partly be attributed to poorly standardized ACA tests reflected in a significant interlaboratory variation in the detection of ACA significant fluctuations of the antibody levels over time in the same patient and very different cut off levels. [17][18][19][20][21][22][23][24] For an obstetrician who is treating patients with recurrent pregnancy loss, previous studies do not adequately answer the question: what are the prognostic value of an elevated ACA titre and the development of late pregnancy complications such as preeclampsia, low birth weight and preterm labour? Therefore, present study objective was to compare the prevalence of ACA in patients with recurrent pregnancy loss and normal healthy pregnant women and its association of complication and obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%